2001
DOI: 10.1074/jbc.m009770200
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Liver-specific Expression of Simian Virus 40 T Antigen Leads to Regulatable Development of Hepatic Neoplasm in Transgenic Mice

Abstract: Adaptive epigenetic changes and toxicity often accompany constitutive expression of a transgene or knockout of an endogenous gene in mice. These considerations potentially limit the usefulness of transgenic technology in studying the in vivo functions of a gene. Using conditional gene expression technology, it is possible to override such restrictions to achieve temporal and tissue-specific manipulation of gene expression in vivo. Based on the tetracycline regulatory system, we established a binary transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Since PIN1 is an enzyme having an extraordinarily high substrate specificity and well-defined active site, it is an ideal target that can potentially be exploited for therapeutic intervention. , and cloned into a pGEM vector under the transcriptional control of a B600 bp fragment of the albumin gene promoter (a kind gift from Dr J Liang, National Institutes of Health, Bethesda, MD, USA) to give the plasmid pPIN1 (Manickan et al, 2001). The PIN1 cDNA clone was sequenced bidirectionally for sequence confirmation.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…Since PIN1 is an enzyme having an extraordinarily high substrate specificity and well-defined active site, it is an ideal target that can potentially be exploited for therapeutic intervention. , and cloned into a pGEM vector under the transcriptional control of a B600 bp fragment of the albumin gene promoter (a kind gift from Dr J Liang, National Institutes of Health, Bethesda, MD, USA) to give the plasmid pPIN1 (Manickan et al, 2001). The PIN1 cDNA clone was sequenced bidirectionally for sequence confirmation.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…In fact, through the use of conditional promoters (e.g. tetracyclineresponsive), it has been shown that continuous expression of LT is required to maintain cellular transformation, as a reversion of the malignant phenotype is observed if LT expression is suppressed (Ewald et al, 1996;Manickan et al, 2001). However, after prolonged LT expression these transformed cells lose their dependence on LT for the maintenance of the transformed state, and remain tumorigenic even after the viral product is no longer expressed (Ewald et al, 1996).…”
Section: How Does T Antigen Action On Cellular Targets Contribute To mentioning
confidence: 99%
“…The role of the J domain has been less studied in transgenic models, and the reports so far indicate an important -although tissue-speci®c-dependency on the J domain to induce tumors (Chen et al, 1992;Ratineau et al, 2000;Symonds et al, 1993). In each of these cases, the amino-terminal fragment of LT is su cient to drive Fox et al, 1989;Zennaro et al, 1998;Le Menuet et al, 2000Bone Behringer et al, 1988Knowles et al, 1990;Jensen et al, 1993;Wilkie et al, 1994 Brain andnervous system Brinster et al, 1984;Reynolds et al, 1988;Chen et al, 1989;Theuring et al, 1990;Chen and Van Dyke, 1991;Perraud et al, 1992;Smith et al, 1992;Jensen et al, 1993;Chiu et al, 2000Cartilage Cheah et al, 1995Digestive system Li et al, 1995Kim et al, 1994;Hauft et al, 1992;Asa et al, 1996Eye Theuring et al, 1990Penna et al, 1998;Beermann et al, 1999Heart Behringer et al, 1988Kidney Theuring et al, 1990Liver Dyer and Messing, 1989Sandgren et al, 1989;Sepulveda et al, 1989;Butel et al, 1990;Manickan et al, 2001Lung Sandmoller et al, 1994Wikenheiser et al, 1992Lymphoid tissue Reynolds et al, 1988Chen et al, 1989Mammary...…”
Section: How Does T Antigen Action On Cellular Targets Contribute To mentioning
confidence: 99%
“…Injection in pronuclei of BALB/ c-fertilized mouse eggs at the one-cell stage was performed by Johannes Wilbertz at the Karolinska Center for Transgene Technologies in Sweden. The transgenic mouse, on a FVB/n genetic background, containing tetracycline-controlled transcriptional activator (tTA), tet-off under control of the mouse major urinary protein promoter (MUP-tTA), was kindly provided by T. Jake Liang (National Institute of Health, Bethesda, MA) (19). The CMV-reverse tTA (rtTA), tet-on (NMRI outbred) mouse was kindly provided by Uwe Galli (University Hospital of Saarlandes, Homberg/Saar, Germany) with the generous approval of Hermann Bujard (University of Heidelberg, Germany) (22).…”
Section: Generation Of Transgenic Micementioning
confidence: 99%